PENGARUH KOMPETENSI,KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP MOTIVASI KERJA PADA PEGAWAI KANTOR CAMAT DI KOTA SUNGAI PENUH - Mauledy Ahmad; Marwan Usman (Program Studi Magister Manajemen, 2015)
The research is proposed to the influence of : 1) Competention to job motivation to civil servants Sungai Penuh Camat Officer, 2) Compenzation and work environment to job motivation to civil servants Sungai Penuh Camat Officer, 3) Work environment to job motivation to civil servants Sungai Penuh Camat Officer. The population in this research were to civil servants Sungai Penuh Camat Officer size of 115 civil servants. Furthermore, by using the formula Slovin, then elected a sample size of 90 civil servants Sungai Penuh Camat Officer with sample tecnique is used namely Simple Random Sampling. The data which namely primer data and skunder data used in this research. For analyzing data by using multiple linear regression analysis and research hipothesis by using testing t with SPSS version 20 is used to analyze the data. The analyze result shows that the competention, compenzation and work environment to cause the positive and significant to job motivation. Keywords : Competention, Compenzation, Work Environment, Job Motivation